INVESTIGATION OF DYNAMIC STABILITY OF FLEXIBLE WAVEGUIDES FOR ULTRASONIC THROMBECTOMY - D. A. Stepanenko; V. T. Mincheny (Наука и техника)
The paper presents results of mathematical modelling of dynamic stability of flexible ultrasonic waveguides applied in engineering and medicine, particularly, in minimally-invasive surgery. By means of the Bubnov-Galerkin method an equation of parametric flexural vibrations of a waveguide is reduced to the Mathieu equation. Stability of the equation solutions is determined by values of its coefficients and may be represented graphically by means of the Ince-Strutt diagram. Parameters of the Mathieu equation determining the stability of its solution are determined by means of finite element method using ANSYS software and APDL programming language.